High TSTA3 Expression as a Candidate Biomarker for Poor Prognosis of Patients With ESCC. (18th June 2018) - Yang, Jie; Kong, Pengzhou; Yang, Jian; Jia, Zhiwu; Hu, Xiaoling; Wang, Zianyi; Cui, Heyang; Bi, Yanghui; Qian, Yu; Li, Hongyi; Wang, Fang; Yang, Bin; et al.
Esophageal squamous cell carcinoma is the sixth most lethal cancer worldwide and the fourth most lethal cancer in China. Tissue-specific transplantation antigen P35B codifies the enzyme GDP-d -mannose-4, 6-dehydratase, which participates in the biosynthesis of GDP-l -fucose. GDP-l -fucose is an important substrate involved in the biosynthesis of many glycoproteins. Cancer cells are often accompanied by the changes in glycoprotein structure, which affects the adhesion, invasion, and metastasis of cells. It is not clear whether tissue-specific transplantation antigen P35B has any effect on the development of esophageal squamous cell carcinoma. We used an immunohistochemical method to assess the expression of tissue-specific transplantation antigen P35B in 104 esophageal squamous cell carcinoma samples. The results showed tissue-specific transplantation antigen P35B expression was associated with some clinical features in patients, such as age ( P = .017), clinical stage ( P = .010), and lymph node metastasis ( P = .043). Kaplan-Meier analysis and log-rank test showed that patients with esophageal squamous cell carcinoma having high tissue-specific transplantation antigen P35B expression had a worse prognosis compared to the patients with low expression ( P = .048). Multivariate Cox proportional hazards regression model showed that high expression of tissue-specific transplantation antigen P35B could predict poor prognosis for patients with esophageal squamous cell carcinoma independently. In conclusion, abnormal fucosylation might participate in the progress of esophageal squamous cell carcinoma and tissue-specific transplantation antigen P35B may serve as a novel biomarker for prognosis of patients with esophageal squamous cell carcinoma.